Learning style, school environment and test anxiety as correlates of learning outcomes among secondary school students (2011)
"The study investigated learning styles, school environment and test anxiety as predictors of learning outcomes among secondary school students. The participants were three hundred senior secondary two students randomly selected from randomly selected secondary schools in Iseyin Local Government Area of Oyo State. Their age ranged between 12 and 19 years with mean age of 15.4 years and the standard deviation of 4.56. The participants were administered four valid and reliable instruments to assess the predictors of learning outcomes among the students (learning styles, school environment and test anxiety). Pearson’s Product Moment Correlation and Multiple regression analysis were used to analyse the data. The result demonstrated that learning styles, school environment and test anxiety jointly predicts the learning outcomes but test anxiety is the most potent predictor of learning outcomes. The implications of the findings for educational and counselling practice were highlighted. "